Validation of a Highly Sensitive RP-HPLC Method for Quantification of Fenofibrate in Pure and Pharmaceutical Dosage Forms - Mehmood Yousaf, Abid; Wuk Kim, Dong; Choi, Han-Gon; Oh, Euichaul (Current Pharmaceutical Analysis, 2014)
A simple, sensitive, specific, robust, precise and accurate reverse-phase high performance liquid chromatographic (RP-HPLC) method was developed and validated for suitable quantitation of fenofibrate in bulk and pharmaceutical dosage forms. The investigation of various validation parameters such as system suitability, linearity, detection limit, quantification limit, precision, accuracy, specificity, robustness and stability was accomplished in accordance with the International Conference on Harmonization (ICH) guidelines. The isocratic elution of fenofibrate was performed using Agilent 1260 Infinity HPLC system. The column was Capcell PAK C18 (4.6 mm x 250 mm, 5 μm). The mobile phase, consisted of acetonitrile and 0.1% (v/v) H3PO4 (75:25, v/v), was eluted at 2 ml/min. The eluent was monitored at 286 nm by the UV detector for fenofibrate concentration measurement. Stability test proved that fenofibrate in sample solutions remained stable at room temperature throughout the analytical process. The limit of detection (LOD) and limit of quantification (LOQ) furnished by this method were better than those of the previously reported HPLC and some UPLC methods of fenofibrate determination. All other validation parameters appeared within the acceptable limits.
Keywords: dosage form